Reactive melt infiltration as synthesis route for enhanced SiC/CoSi2 composite materials for advanced armor systems. Issue 11 (1st August 2018) - Caccia, Mario; Xiang, Chongchen; Narciso, Javier; Gupta, Nikhil
Abstract: Advanced ceramics such as silicon carbide (SiC) have shown an excellent performance under impact loading, and given their low density, they have attracted attention to be used in personal armor as well as in vehicles. Sintered SiC presents, nevertheless, an elevated cost which is a direct consequence of the severe temperature and pressure conditions required to sinter it. Reactive melt infiltration is a more cost-effective way to obtain SiC-based materials. It is a pressureless technique that requires much lower temperatures (1450–1600 °C) and provides extra near-net shape capabilities, thus reducing the processing cost of the final material. The main disadvantage of this technique is that the final material presents a variable content of unreacted Si in its microstructure (5–25 vol%). Due to its lower mechanical properties Si usually hinders the overall performance of the material. The replacement of the unreacted Si phase in SiC-based composites produced by reactive melt infiltration remains one of the biggest challenges that limits the applications of such materials. In this work, an alternative route is proposed, using Si-rich Si-Co alloys as infiltrants to replace the weaker Si phase with a tougher CoSi2 phase. The thermo-mechanical properties of the produced composites have been measured and correlated to its microstructure. The presence of CoSi2 showed up to 200% improvement in the impact performance of the composites.